Surgical procedures for voice restoration - Nawka, Tadeus (German Medical Science, 2005)
Surgical procedures for voice restoration serve to improve oral communication by better vocal function. They comprise of phonomicrosurgery, with direct and indirect access to the larynx; laryngoplasty; laryngeal injections; and surgical laryngeal reinnervation. The basis for modern surgical techniques for voice disorders is the knowledge about the ultrastructure of the vocal folds and the increasing experience of surgeons in voice surgery, while facing high social and professional demands on the voice. Vocal activity limitation and participation restriction has become more important in the artistic and social areas. A number of surgical methods that have been developed worldwide for this reason, are presented in this article. Functional oriented surgery has to meet high standards. The diagnostics of vocal function has to be multi-dimensional in order to determine the indication and the appropriate surgical intervention.